A plasma metabonomics study on the therapeutic effects of the Si-miao-yong-an decoction in hyperlipidemic rats. (28th June 2020) - Shi, Shan; Liu, Ziying; Xue, Zhengyuan; Chen, Xiaohui; Chu, Yang
Abstract: Ethnopharmacological relevance: The Si-miao-yong-an decoction (SMYAD) is a famous traditional Chinese medicinal formula that has been used for centuries in ancient China for treating thromboangiitis obliterans. Because of its long history of use, it has been used to treat patients in China for thousands of years. In recent years, SMYAD has been widely used for treating cardiovascular and endocrine diseases. It was shown to significantly increase high-density lipoprotein-cholesterol levels and reduce total cholesterol and low-density lipoprotein-cholesterol levels in the serum. Aim of the study: Herein, a serum metabonomics approach based on the HPLC-MS/MS method was adopted to evaluate the therapeutic effect of SMYAD on high-fat diet-induced hyperlipidemia, and investigate the mechanisms for treating hyperlipidemia. Materials and methods: Firstly, the change in body weight, liver histopathology, and serum biochemistry, including that in the levels of hepatotoxicity-related enzymes, oxidative stress indexes, and inflammatory factors were monitored in rats, to evaluate the therapeutic effect of SMYAD on high-fat diet-induced hyperlipidemia. Then, a serum metabolomics approach was applied, to cluster different groups using principle component analysis (PCA) and partial least squares discriminant analysis (PLS-DA), as well as to screen out sensitive and reliable biomarkers. Finally, the metabolic pathways associated with specific biomarkers were analyzed, to understand the possible mechanism underlying the action of SMYAD. Results: The results indicated that SMYAD had significant anti-hyperlipidemic, anti-oxidant, and anti-inflammatory effects. Based on the results of serum metabolomics analysis, the hyperlipidemic rats showed completely different results compared to the control rats; metabolite profiles of rats from the SMYAD treatment groups showed a trend comparable to those of the normal control group in a dose-dependent manner. Besides, twelve biomarkers associated with pyruvate metabolism, taurine and hypotaurine metabolism, TCA cycle, bile acid metabolism, and glucose metabolism were identified and confirmed, to clarify the mechanism of action of SMYAD. Conclusion: Using metabonomics technology, it was predicted that the therapeutic effects of SMYAD were associated with its anti-oxidation as well as anti-inflammatory activities and the adjustment of the pyruvate, taurine as well as hypotaurine metabolism pathways in the hyperlipidemic state. This study provided evidence regarding the clinical application of SMYAD and thoroughly explored the mechanism underlying the action of this traditional Chinese medicine. Graphical abstract: Image 1